A Modern Approach to the Early Diagnosis and Treatment of Chronic Diseases of the Oral Mucosa (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Over the past decade, the problem of prevention and treatment of chronic diseases of the oral mucosa has been given considerable attention by domestic and foreign researchers [1, 2, 3, 4, 5, 6, 7, 8]. This is primarily due to an increase in the negative impact of immunosuppressive environmental factors on the human body, the widespread and not always justified use of drugs with antibacterial properties [9, 10, 11, 12, 13, 14]. The results of the analysis of literature data on chronic diseases of the oral mucosa are presented.